Creating supported plasma membrane bilayers using acoustic pressure - Sezgin, E; Carugo, D; Levental, I; Stride, E; Eggeling, C (MDPI, 2020)
Model membrane systems are essential tools for the study of biological processes in a simplified setting to reveal the underlying physicochemical principles. As cell-derived membrane systems, giant plasma membrane vesicles (GPMVs) constitute an intermediate model between live cells and fully artificial structures. Certain applications, however, require planar membrane surfaces. Here, we report a new approach for creating supported plasma membrane bilayers (SPMBs) by bursting cell-derived GPMVs using ultrasound within a microfluidic device. We show that the mobility of outer leaflet molecules is preserved in SPMBs, suggesting that they are accessible on the surface of the bilayers. Such model membrane systems are potentially useful in many applications requiring detailed characterization of plasma membrane dynamics.